the answer is C.
A false statement implies a true statement , so the conditional statement is true.
Answer:2
Step-by-step explanation: that ez
(0, 0) → t = 0, w = 0 → w = 0 · 0
(1, 4) → t = 1, w = 4 → w = 1 · 4
(2, 8) → t = 2, w = 8 → w = 2 · 4
(3, 12) → t = 3, w = 12 → w = 3 · 4
<h3>Answer: w = 4t</h3>
Step 1 :
(23 x 2 - 5) • x 3
Step 2 :
Trying to factor as a Difference of Squares :
Factoring: 8 x 2-5
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Answer:
(8 x 2 - 5) • x 3